Journalism : theory, practice and criticism - Tumber, Howard; Zelizer, Barbie (London : SAGE, 2015)
Journalism theory, practice and criticism journal contributes to the social, economic, political, cultural and practical understanding of journalism, covering current development and historical changes within the field.
Existing both in print and electronics/E-resource.
Includes bibliographical references.
Keywords: Journalism - Periodicals; Journalism - Study and teaching - Periodicals